Exploration of the Utilization of Sweet Potato Leaf Meal as a Phytobiotic Feed Additive in the Development of Beef Cattle Green Farms in Bone Regency - Astati; Amriana Hifizah; Anas Qurniawan; Muhammad Khalifah Mustami (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2026)
The development of sustainable beef cattle farming through the utilization of eco-friendly local resources is crucial to supporting the transformation of the green farm system in Indonesia. One potential innovation is the use of natural phytobiotic-based feed ingredients to enhance livestock health and productivity. This research aims to explore the potential utilization of sweet potato leaf meal as a phytobiotic feed additive in beef cattle farming within Bone Regency, South Sulawesi Province. The research method employed is a qualitative field study approach conducted through in-depth interviews, direct observation, and documentation. The research informants include beef cattle farmers, agricultural extension workers, and academics selected using a purposive sampling technique. Data analysis was carried out through the stages of data reduction, data display, and thematic conclusion drawing. The results of the study indicate that sweet potato leaves contain bioactive compounds such as flavonoids, tannins, saponins, and antioxidants, which have the potential to improve livestock health, enhance the digestive system, and increase the efficiency of feed nutrient utilization. The utilization of sweet potato leaf meal is also considered capable of reducing dependence on synthetic antibiotics and commercial feed, lowering production costs, and optimizing the use of agricultural waste. However, implementation at the farmer level still faces obstacles in the form of limited knowledge, simple processing technology, and the lack of standardization for phytobiotic feed formulations. This study concludes that sweet potato leaf meal has great prospects as a phytobiotic innovation in supporting the sustainability of green farms in Bone Regency.